2012
DOI: 10.2478/10004-1254-63-2012-2246
|View full text |Cite
|
Sign up to set email alerts
|

Associations between weather conditions and ragweed pollen variations in Szeged, Hungary

Abstract: This study analyses potential associations between day-to-day variations in common ragweed pollen counts in the southern Hungarian district of Szeged and meteorological variables using adapted factor analysis. The database includes ten years (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) worth of data on daily common ragweed pollen ratios (value on the given day per value on the day before) and daily differences (value on the given day minus value on the day before) in eight meteorological variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Concerning extreme weather events, the coldest and the wettest years highly facilitate Ambrosia pollen production, while both for Poaceae and Populus, the warmest and wettest years favour higher pollen release . Furthermore, Matyasovszky et al (2012) established a tendency to stronger associations between the meteorological variables and the ragweed pollen variable in the pre-peak pollen season, compared to the post-peak pollen season (late summer to early autumn) that is confirmed by Giner et al (1999) and Laaidi (2001). This is in accordance with the statement of Makra et al (2014) who found that definitely stronger associations between the meteorological variables and the Poaceae pollen variable are found in the data sets for lower summer temperatures with near-optimum phyto-physiological processes compared to those for high and extreme high temperatures modifying life functions and, accordingly, interrelationships of the meteorological and pollen variables.…”
Section: Ambrosia Multiple Correlationsmentioning
confidence: 99%
“…Concerning extreme weather events, the coldest and the wettest years highly facilitate Ambrosia pollen production, while both for Poaceae and Populus, the warmest and wettest years favour higher pollen release . Furthermore, Matyasovszky et al (2012) established a tendency to stronger associations between the meteorological variables and the ragweed pollen variable in the pre-peak pollen season, compared to the post-peak pollen season (late summer to early autumn) that is confirmed by Giner et al (1999) and Laaidi (2001). This is in accordance with the statement of Makra et al (2014) who found that definitely stronger associations between the meteorological variables and the Poaceae pollen variable are found in the data sets for lower summer temperatures with near-optimum phyto-physiological processes compared to those for high and extreme high temperatures modifying life functions and, accordingly, interrelationships of the meteorological and pollen variables.…”
Section: Ambrosia Multiple Correlationsmentioning
confidence: 99%
“…This is due to the difference in the behaviour of the plant to stand environmental stress. Namely, the data set for which A  1.00 can be associated to lower summer temperatures with near-optimum phyto-physiological processes, while the category of A  1.00 is involved with high and extreme high temperatures modifying life functions and, hence, interrelationships of the meteorological and pollen variables (Tables 1-3) Matyasovszky et al, 2012b;.…”
Section: Discussionmentioning
confidence: 99%